2009
DOI: 10.1371/journal.pmed.1000146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Duration and Intermittency of Rifampin on Tuberculosis Treatment Outcomes: A Systematic Review and Meta-Analysis

Abstract: In a systematic review of randomized controlled trials on tuberculosis treatment, Dick Menzies and colleagues find shorter courses of rifampin to be associated with poorer treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(152 citation statements)
references
References 58 publications
6
133
1
2
Order By: Relevance
“…Two studies which compared the use of RIF to the use of ethambutol (ETB) in the continuation phase after initial treatment with isoniazid (INH)-RIF-pyrazinamide (PZA)-ETB found that those on ETB-INH were 2 to 3 times more likely to experience treatment failure or TB relapse than those on RIF-INH for continuation therapy (135,204). Several meta-analyses have shown that treatment with a longer duration (6 months or longer) of a rifamycin drug (rifampin or rifabutin [RfB]) resulted in lower rates of failure and recurrence and improved survival during treatment, compared to only 2 months of treatment with a rifamycin drug (146,150,186). More recent data suggest that a duration of rifampin treatment even longer than the recommended 6 months may decrease failure and recurrence rates even further (146,239).…”
Section: Treatment Of Tb For Hiv-infected Patients: Rifampin Combinatmentioning
confidence: 99%
“…Two studies which compared the use of RIF to the use of ethambutol (ETB) in the continuation phase after initial treatment with isoniazid (INH)-RIF-pyrazinamide (PZA)-ETB found that those on ETB-INH were 2 to 3 times more likely to experience treatment failure or TB relapse than those on RIF-INH for continuation therapy (135,204). Several meta-analyses have shown that treatment with a longer duration (6 months or longer) of a rifamycin drug (rifampin or rifabutin [RfB]) resulted in lower rates of failure and recurrence and improved survival during treatment, compared to only 2 months of treatment with a rifamycin drug (146,150,186). More recent data suggest that a duration of rifampin treatment even longer than the recommended 6 months may decrease failure and recurrence rates even further (146,239).…”
Section: Treatment Of Tb For Hiv-infected Patients: Rifampin Combinatmentioning
confidence: 99%
“…Clinical data for the impact of drug pressure on de novo drug resistance evolution stem mostly from infections requiring long-lasting treatment such as HIV [32][33][34] and TB [35]. For HIV-1, studies considering resistance evolution in relation to patient adherence suggest that treatment that does not completely suppress pathogen replication facilitates de novo evolution of resistance [32 -34,36].…”
Section: Empirical Evidencementioning
confidence: 99%
“…There is concern that the development of acquired rifamycin monoresistance (ARR), treatment failure, and relapse may be associated with intermittent dosing (4,20), insufficient companion drug exposure (33), or low rifamycin concentrations (9,21). RFP's sterilizing effect has been shown to be dose dependent in murine studies which suggest that daily doses of RFP may reduce treatment duration to just 3 months (25,26,37), and higher doses of RFP are associated with improved early bactericidal activity in humans (29).…”
mentioning
confidence: 99%